Study of transient phenomena using NI-USB data acquisition systems in Matlab-Simulink medium on 64 bit operating systems - Titu, Niculescu (Journal of Advanced Computer Science & Technology, 2015)
The paper presents a new and modern method for study the transient phenomena appeared to connect the capacitive charges to an AC power source, using the MATLAB-SIMULINK software package. It is known that NI-USB data-acquisition systems manufactured by National Instruments are not seen by Simulink software package in 64-bit systems. For this is obligatory for use a 32-bit system. From this point of view, the article presents a method by which this disadvantage is eliminated, making possible the data acquisition process in Simulink software package.